Adult education history in Britain: past, present and future (part I). (3rd May 2020) - Freeman, Mark
ABSTRACT: This article – the first part of a two-part contribution – considers the current and past state of research on the history of adult education in Britain. Although there has been a broadening of interest among historians of adult education, the field remains to an extent in the shadow of the "Great Tradition" of liberal education epitomised by university tutorial classes and the Workers' Educational Association, as well as the contested historiography of independent working-class education. The article takes issue with three distinctions that have been widely made in the literature: between vocational and non-vocational education, between different motivations for participation in adult learning, and between "sponsored" and "independent" working-class education. It is shown that these distinctions are productively undermined by a shift in the focus of historiography from education to learning, and in particular by the growing interest among historians in popular reading and writing practices in the past. This is one of a number of ways in which the history of adult education has overlapped with, and contributed to, other areas of historical research.